Edukasi COVID-19 pada Warga Madras Hulu Petisah Tengah Medan - Ahmad Purnawarman Faisal (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2022)
Coronavirus 2019 (Covid-19) is an infectious disease caused by the acute respiratory syndrome coronavirus 2 (Sars-CoV-2). The outbreak of this disease has shaken the world community so much, that almost 200 countries in the world have been infected by this virus, including Indonesia. Various efforts to prevent the spread of the Covid-19 virus have also been carried out by governments in countries around the world to break the chain of the spread of the Covid-19 virus, which is referred to as lockdown and social distancing. The method used in this community service activity is the participatory community empowerment method with the Particatory Rural Appraisal (PRA) model, which is a method that emphasizes community involvement in all activities carried out. This Community Service is carried out with COVID-19 counseling and COVID-19 Pharmacology Therapy. Results of Community Service Respondents have been exposed to COVID-19 and how to prevent it with health protocols according to the WHO circular and the COVID-19 Task Force. The category of respondents' knowledge about COVID-19 has increased from 11.5% to 94.3%.